2002
DOI: 10.1152/ajprenal.00199.2001
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated buffering of renal perfusion pressure variation in juxtamedullary cortex in SHR

Abstract: Renal tissue damage is substantially more pronounced in the juxtamedullary than in the superficial cortex in hypertensive rats, and the pathogenesis of the morphological changes are only partly understood. Glomerular capillary pressure (PGC) is increased, and steady-state autoregulation is normal in the deep renal cortex. We tested the hypothesis that the transient period from one pressure level to another may induce greater variation in local perfusion before stable autoregulation is established. An acute inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
5
18
0
Order By: Relevance
“…In the hypertensive animal, proteinuia develops from juxtamedullary nephrons and P GC is higher in glomeruli in juxtamedullar than superficial glomeruli in hypertensive rats (11). The early development of juxtamedullary degeneration in hypertensive animals has also been supported by a recent study where we found that autoregulation of renal blood flow (RBF) was less effective in hypertensive than in normotensive animals and less effective in inner than in outer cortex, i.e., pattern similar to that seen in glomerulosclerosis and tubular degeneration (27).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…In the hypertensive animal, proteinuia develops from juxtamedullary nephrons and P GC is higher in glomeruli in juxtamedullar than superficial glomeruli in hypertensive rats (11). The early development of juxtamedullary degeneration in hypertensive animals has also been supported by a recent study where we found that autoregulation of renal blood flow (RBF) was less effective in hypertensive than in normotensive animals and less effective in inner than in outer cortex, i.e., pattern similar to that seen in glomerulosclerosis and tubular degeneration (27).…”
supporting
confidence: 71%
“…In the hypertensive animal, proteinuia develops from juxtamedullary nephrons and P GC is higher in glomeruli in juxtamedullar than superficial glomeruli in hypertensive rats (11). The early development of juxtamedullary degeneration in hypertensive animals has also been supported by a recent study where we found that autoregulation of renal blood flow (RBF) was less effective in hypertensive than in normotensive animals and less effective in inner than in outer cortex, i.e., pattern similar to that seen in glomerulosclerosis and tubular degeneration (27).Proteinuria has been suggested to be the main pathogenic factor in tubular degeneration, whereas P GC and increased stretch are thought to be important in the development of the glomerulosclerosis. The primary intention of the present study was to conduct experiments to demonstrate a parallel progression of glomerulosclerosis and tubular damage in Wistar-Kyoto rats (WKY) and spontaneously hypertensive rats (SHR).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…This may relate to the observation that the intermediate segments of the interlobular artery in this strain exhibit an enhanced myogenic response (69), which would provide added protection for the distal superficial glomeruli but not the juxtamedullary nephrons. Autoregulatory responses are also reported to be slower in the juxtamedullary cortex of the aged SHR (127), and this could contribute to the pattern of injury. Finally, when autoregulatory capacity in the SHR is reduced by 5/6 renal ablation, these animals rapidly develop malignant nephrosclerosis (17).…”
Section: Consequences Of Impaired Renal Autoregulation On Renal Protementioning
confidence: 99%
“…Interestingly, it is reported that in SHRs, such transient changes in glomerular capillary pressure of the juxtamedullary nephron are much greater than in normotensive Wistar-Kyoto rats. 46 In addition, micropuncture studies have shown that only juxtamedullary (but not superficial) glomerular capillary pressure is elevated in SHR as compared with WKY, and this elevation becomes prominent in old SHRs. 31 Finally, it is reported that uninephrectomy causes selective deep nephron hyperfiltration in SHRs but not in WKY.…”
Section: Albuminuria and Endothelial Dysfunctionmentioning
confidence: 99%